2017
DOI: 10.1097/md.0000000000007114
|View full text |Cite
|
Sign up to set email alerts
|

Overall evaluation of the clinical value of prenatal screening for fetal-free DNA in maternal blood

Abstract: Objective:To explore the clinical value of prenatal screening for fetal-free DNA in maternal blood.Methods:A total of 10,275 maternal blood samples were collected from October 2012 to May 2016 at the prenatal diagnosis center of Changzhou Woman and Children Health Hospital.Results:Among 10,275 pregnant women accepted noninvasive prenatal testing (NIPT), 9 cases could not get the results after collected the blood second times. The rate of NIPT failure was 0.09%. Seventy-two cases got the NIPT positive results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 10 publications
3
39
0
Order By: Relevance
“…Our results suggest that NIPT is suitable for high-and intermediate-risk prenatal screening. It has been reported that among 56 Down syndrome fetuses, 14% were associated with intermediate-risk mothers [22]. In our study, NIPT for intermediate-risk samples detected 10 positive cases, among which 7 were true positive (70.00%).…”
Section: Discussionsupporting
confidence: 46%
“…Our results suggest that NIPT is suitable for high-and intermediate-risk prenatal screening. It has been reported that among 56 Down syndrome fetuses, 14% were associated with intermediate-risk mothers [22]. In our study, NIPT for intermediate-risk samples detected 10 positive cases, among which 7 were true positive (70.00%).…”
Section: Discussionsupporting
confidence: 46%
“…Similarly, the PPV of T21/T18/T13 in AMA was all higher than the total samples in the present study. In a previous study, the efficiency of NIPT among 3585 advanced maternal age women was higher than the total samples too [7].…”
Section: Discussionmentioning
confidence: 76%
“…NIPT is rapidly being adopted as to screening test for the detection of fetal aneuploidies of chromosomes 13, 18, and 21 [5,6], and this method is also available for the detection of sex chromosome aneuploidies (SCAs ) [7]. A recent meta-analysis showed that the weighted pooled detection rate (DR) and false-positive rate (FPR) for T21 were 99.7% (95% CI, 99.1-99.9%) and 0.04% (95% CI, 0.02-0.07%), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, noninvasive prenatal screening (NIPS) was regarded as a good choice for AMA pregnant women. It could not only achieve satisfactory clinical effect, but also greatly reduce invasive prenatal diagnosis (11). AMA women were also willing to accept it and became the largest population for NIPS testing (12).…”
Section: Introductionmentioning
confidence: 99%